2004
DOI: 10.1016/s0026-2714(03)00216-6
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial methods for the evaluation of yield and operational reliability of fault-tolerant systems-on-chip

Abstract: In this paper we develop combinatorial methods for the evaluation of yield and operational reliability of fault-tolerant systems-on-chip. The method for yield computation assumes that defects are produced according to a model in which defects are lethal and affect given components of the system following a distribution common to all defects; the method for the computation of operational reliability also assumes that the fault-tree function of the system is increasing. The distribution of the number of defects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…However, experiments in [15] indicated that that method has a much larger computational cost than the method proposed in this paper and is able to handle efficiently only SoCs with up to a few tens of components. As a confirmation, the method was not able to analyze any of the five benchmarks considered in this paper with when run with an error requirement and a memory limitation of 4 GB.…”
Section: Discussion Of Alternativesmentioning
confidence: 88%
See 3 more Smart Citations
“…However, experiments in [15] indicated that that method has a much larger computational cost than the method proposed in this paper and is able to handle efficiently only SoCs with up to a few tens of components. As a confirmation, the method was not able to analyze any of the five benchmarks considered in this paper with when run with an error requirement and a memory limitation of 4 GB.…”
Section: Discussion Of Alternativesmentioning
confidence: 88%
“…There seem to be only three immediate alternatives to the proposed method: the combinatorial method described in [15], the so-called "compounding technique" (see, e.g., [13]), and simulation. The compounding technique can only be used with compound Poisson models.…”
Section: Discussion Of Alternativesmentioning
confidence: 99%
See 2 more Smart Citations